'Bacteroides cutis, ' a new bacterial species isolated from human skin. (March 2018) - Belkacemi, S.; Cassir, N.; Delerce, J.; Cadoret, F.; La Scola, B.
Abstract: We report the main characteristics of 'Bacteroides cutis' sp. nov., strain Marseille-P4118 T (= CSUR P4118), a new species within the genus Bacteroides . This strain was isolated from a skin sample of a 75-year-old man from Marseille.